Multidisciplinary interface model for design of mechatronic systems - Zheng, Chen; Le Duigou, Julien; Bricogne, Matthieu; Eynard, Benoît (Computers in industry, 2016)
•We propose a new data model for design and integration of mechatronic systems.•We develop this new model for improving design methodology.•We present the integration of multidisciplinary interfaces in mechatronic systems.•We detail the model implementation to illustrate the methodology application. The design of mechatronic systems is based on the integration of several disciplines, such as mechanical, electrical and software engineering. How to achieve an integrated multidisciplinary design during the development process of mechatronic systems has attracted the attention of both academia and industry. However, solutions which can fully solve this problem have not been proposed by now. The concept of multidisciplinary interface represents the logical or physical relationship integrating the components of the mechatronic system or the components with their environment. As the design of mechatronic systems is a multidisciplinary work, the multidisciplinary interface model can be considered as one of the most effective supports to aid designers for achieving the integrated multidisciplinary design during the development process. The paper presents a multidisciplinary interface model for design of mechatronic systems in order to enable the multidisciplinary integration among design team members from different disciplines. On the one hand, the proposed model ensures the consistency of interface defined by the designers. On the other hand, it helps the designers to guarantee the different components integrate correctly. The interface model including three concepts: classification, data model and compatibility rules. The multidisciplinary interface model is implemented by a case study based on a 3D measurement system.